Research of Offset Correction System of Tipping Paper on Cigarette-rolling Machine - Li Yongjie; Zhou Rui (Jixie chuandong)
For the length deviation of cigarette products tipping paper and the shortage of direction correction device on cigarette- rolling machine,the causes of the offset of the tipping paper transmission is analyzed.The direction automatic offset correction system is researched and developed for tipping paper on cigarette- rolling machine,and the feeding system accuracy of tipping paper can be ensured,the length deviation of tipping paper during the cigarette- rolling process is improved,and the cigarette product quality is significantly improved.